A pervasive typographical error in an equation for calculating nectar density is likely to have limited consequences - Symington, Hamish; Rockx, Joris (Journal of Pollination Ecology, 2025)
Analysis of floral nectar reward often involves converting nectar volume to sugar mass. Nectar density depends on nectar sugar concentration, and has been empirically measured. A quadratic equation which accurately models sucrose density over a range of concentrations was published in a book in 1987. This equation was restated in a publication in 2001, but with a typographical error transposing two digits in the coefficient of the linear term. The incorrect equation has been used in numerous studies since its publication, including in the generation of large datasets. However, the error in density introduced by the incorrect equation is never more than 0.5%, which is greatly smaller than the standard deviation in published floral measurements of nectar volumes and concentrations. The error is therefore likely to have limited consequences, but we recommend using the more accurate equation for future studies. While exploring this error we found several others, some of which affect reported data and some of which are simple typographical errors introduced while preparing a manuscript. We caution authors to be scrupulous in reporting units and equations relating to nectar measurement.